Moderating effect of and emotional intelligence on the relationship between skills and employability - Aziz, Atif; Pangil, Faizuniah (Human Resource Management Academic Research Society, 2017)
The purpose of the study is to examine moderating role of emotional intelligence on the relationship of perceived soft skills and employability in the business graduates of Malaysia. Study is descriptive and quantitative in nature. The data were collected from 380 students of four different universities (USM, UITM, UUM, UM) of Malaysia. CFA and SEM techniques have been applied to check the validity and hypotheses testing. The results divulged that different types of skills are significantly and positively associated with employability. Moreover, findings also proved that students level of emotional intelligence significantly moderate on the relationship of perceived soft skills and employability. This study gives insight understanding regarding the crucial role of skills and emotional intelligence to positively shape the employability.